Interaksi Komponen Komunikasi Interpersonal oleh Pramusapa di Layanan Transjakarta - Surya, Elizabeth; Aulia, Sisca (Kiwari, 2025)
This research discusses the interpersonal communication interactions of waiters on Transjakarta services. Transjakarta is a public transportation company that is part of a Regional Owned Enterprise (BUMD) with the first Bus Rapid Trans Jakarta transportation system in the Southeast and South Asia region. After operating for 11 years, Transjakarta is actively developing performance, coverage, service quality and sustainability of services. Communication is an important factor in determining the success of a company's services. Therefore, this research aims to find out how the interpersonal communication interactions of waiters in Transjakarta services work. This research uses Interpersonal Communication Theory and uses a qualitative approach with an interview method. The results of the research show that the interpersonal communication interactions of waiters in Transjakarta Services include interpersonal communication components, namely sender-receiver, encodingdecoding, messages, channels, interference, feedback, areas of experience, and effects. Apart from that, equal collaboration between interpersonal communication and consistency in carrying out the company's vision, mission and values is able to create effective interpersonal communication interactions through service by Transjakarta attendants. This is what makes customers feel respected and appreciated. Penelitian ini membahas interaksi komunikasi interpersonal pramusapa di layanan Transjakarta. Transjakarta merupakan perusahaan transportasi umum yang menjadi bagian dari Badan Usaha Milik Daerah (BUMD) dengan sistem transportasi Bus Rapid Trans Jakarta pertama di kawasan Asia Tenggara dan Selatan. Setelah beroperasi selama 11 tahun Transjakarta giat mengembangkan kecakapan, lingkup, taraf pelayanan, dan persisten dari layanan. Komunikasi menjadi faktor penting dalam menentukan keberhasilan pelayanan sebuah perusahaan. Oleh karena itu, penelitian ini bertujuan untuk mengetahui bagaimana interaksi komunikasi interpersonal yang dilakukan oleh pramusapa Transjakarta. Penelitian ini menggunakan teori komunikasi interpersonal dan menggunakan pendekatan kualitatif dengan metode wawancara. Hasil penelitian menunjukkan bahwa adanya interaksi komunikasi interpersonal yang dilakukan oleh pramusapa Transjakarta meliputi komponen-komponen komunikasi interpersonal, yaitu pengirim-penerima, encoding-decoding, pesan-pesan, saluran, gangguan, umpan balik, bidang pengalaman, dan efek. Selain itu, kolaborasi sepadan antara komunikasi interpersonal dan konsistensi untuk menjalankan visi misi serta nilai perusahaan mampu menciptakan interaksi komunikasi interpersonal yang efektif melalui pelayanan oleh pramusapa Transjakarta. Hal ini lah yang membuat pelanggan merasa dihormati dan dihargai.